2020
DOI: 10.1186/s12903-020-01195-3
|View full text |Cite
|
Sign up to set email alerts
|

Parental acceptance of silver Diamine fluoride application on primary dentition: a systematic review and meta-analysis

Abstract: Background This systematic review of the literature was carried out to assess parental acceptance for silver diamine fluoride (SDF) application and esthetic outcome on their children primary dentition and evaluate factors that might influence their acceptance. Methods Our research protocol included a search strategy, inclusion/exclusion criteria, and a data extraction plan. The search engines we used were PubMed, Google Scholar, and Science Direct. Reviewers independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 29 publications
1
47
0
3
Order By: Relevance
“…One reported that only 53.3% of parents considered SDF treatment for their children acceptable due to discoloration problems [23]. Sabbagh et al showed that parental acceptance of SDF treatment was significantly higher for posterior teeth than for anterior teeth [22]. Hence, this study aimed to quantify the color change produced by SDF in primary molars as well as the masking effect of the KI bleaching agent and CMP and GI restorations.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…One reported that only 53.3% of parents considered SDF treatment for their children acceptable due to discoloration problems [23]. Sabbagh et al showed that parental acceptance of SDF treatment was significantly higher for posterior teeth than for anterior teeth [22]. Hence, this study aimed to quantify the color change produced by SDF in primary molars as well as the masking effect of the KI bleaching agent and CMP and GI restorations.…”
Section: Discussionmentioning
confidence: 98%
“…However, how to reduce the discoloration associated with the application of SDF in primary teeth remains unclear. Several studies have tried to measure the parental acceptance of SDF application in children [22]. One reported that only 53.3% of parents considered SDF treatment for their children acceptable due to discoloration problems [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many published studies have focused on parental acceptance of SDF, [28][29][30] but to our knowledge, few studies have reported on the actual use of SDF in clinical practice. In this pediatric dentistry practice, SDF was presented to parents as a treatment option in every situation where a child's needs were unable to be managed in a timely manner.…”
Section: Discussionmentioning
confidence: 99%
“…Parental perception of SDF was variable in literature. A systematic review conducted by Sabbagh et al (12) in 2020, concluded that tolerance to SDF was significantly higher in posterior teeth than anterior ones and in uncooperative children than cooperative ones. They also recommended giving pre-operative instructions to the parents which had a significant positive impact on parental acceptance to SDF treatment.…”
Section: Introductionmentioning
confidence: 99%